Student experiences in art Learning based on creative pedagogy: Pengalaman mahasiswa dalam seni rupa berbasis pedagogi kreatif - Wicaksana, Arya; Amalia, Reza; Damanik, Eva Agnesia Rayani; Jannah, Fatihah Ghoziyatul; Syakira, Afrah; Nugraha, Bandhung Galih (Sungging: Journal of Innovative, Cultural, Transdisciplinary Art and Kriya Discourse, 2025)
This study examines the experiences of fourth-semester Art Education students with creative pedagogy-based art learning. Using a phenomenological approach, data were collected through in-depth interviews with four participants in the Videography course. Thematic analysis revealed that creative pedagogy facilitates freedom of expression, the utilisation of imagination, and the exploration of personal style. Students reported deeper emotional and reflective engagement in learning, along with enhanced artistic identity development through autonomous selection of media, themes, and techniques. Significant differences were noted compared to conventional instruction's rigid, technical approach. Thus, creative pedagogy proves relevant for Art education, supporting character development and students' readiness in confronting the challenges of contemporary art and the demands of the creative industry.   _______________________________________________________________________________   Penelitian ini mengeksplorasi pengalaman mahasiswa semester IV Pendidikan Seni Rupa dalam pembelajaran seni berbasis creative pedagogy. Metode fenomenologi digunakan dengan wawancara mendalam terhadap empat partisipan mata kuliah Videografi. Hasil analisis tematik menunjukkan pendekatan ini memfasilitasi kebebasan berekspresi, pemanfaatan imajinasi, dan eksplorasi gaya personal. Mahasiswa merasa lebih terlibat secara emosional dan reflektif, serta mampu mengembangkan identitas artistik melalui pemilihan media, tema, dan teknik secara mandiri. Perbedaan signifikan terlihat dibanding pembelajaran konvensional yang lebih kaku dan teknis. Dengan demikian, creative pedagogy relevan diterapkan dalam pendidikan seni untuk mendukung pengembangan karakter dan kesiapan mahasiswa menghadapi tantangan seni kontemporer dan industri kreatif.